INTAKE OF MACRO NUTRITION, FIBER, AND SODIUM WORKERS PT MASMINDO DWI AREA: ASUPAN ZAT GIZI MAKRO, SERAT DAN NATRIUM PEKERJA PT MASMINDO DWI AREA - Gina Mujahida Opu Mangeka; Marini Amalia Mansur; Nurzakiah; Safrullah Amir; Nurhaedar Jafar (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Introduction: Mining work is one of the jobs where people are involved in physical hardship and therefore maintaining a good nutritional status is very important. As a result of food intake with unbalanced nutrition, it will result in workers experiencing nutritional problems, such as malnutrition or obesity. Aim: This study aims to describe the intake of macronutrients (energy, carbohydrates, protein, and fat), fiber, and sodium in workers at the Awak Mas Site PT Masmindo Dwi Area. Materials and Methods: This type of research was a quantitative study with a descriptive design with a total sample of 100. The sampling technique in this study was proportional stratified random sampling by taking samples of various categories of workers' physical activity with balanced proportions. Data collection was obtained using a 2x24 hour food recall questionnaire to obtain energy, carbohydrate, protein, fat, fiber, and sodium intake data. Data processing uses the Software Package for Social Science (SPSS) program. Data analysis is presented in a frequency distribution table accompanied by narration. Results: The results showed that, based on their energy intake, 35% had less energy intake, 58% enough and 7% more. Based on protein intake, 15% had less protein intake, 42% enough, and 43% more. Based on fat intake, 32% had less fat intake, 33% enough, and 35% more. Based on carbohydrate intake, 62% had insufficient carbohydrate intake, 37% sufficient, and 1% more. Based on fiber intake, 99% had less fiber intake and 1% had normal fiber intake. Based on sodium intake, 14% had normal sodium intake and 86% had more sodium intake. Conclusion: Workers at Awak Mas Site PT Masmindo Dwi Area have unbalanced food intake, including insufficient intake of carbohydrates and fiber, as well as excess intake of protein, fat and sodium. Thus, it is suggested that workers pay more attention to their food intake by reducing excessive consumption of fat, protein and sodium and increasing their daily intake of carbohydrates and fiber.